Entomopathogenic nematodes and their mutualistic bacteria: Their ecology and application as microbial control agents - Gülcü, Barış; Çimen, Harun; Raja, R.K.; Hazır, Selçuk (Koul Research Foundation, 2017)
Entomopathogenic nematodes (EPNs) belonging to the families heterorhabditidae (genus Heterorhabditis) and steinernematidae (genus Steinernema) are mutualistically associated with bacteria in the family Enterobacteriaceae (Photorhabdus spp. for Heterorhabditis and Xenorhabdus spp. for Steinernema). At present, there are 100 Steinernema and 17 Heterorhabditis species and 20 Xenorhabdus and 4 Photorhabdus species. In general, each EPN species has its own bacterial species, but a given bacterial species may be associated with more than one EPN species. The EPNs' natural habitat is the soil where the nematode-bacterium complex infects many different insect species killing them within 48 h. EPNs have been isolated from many different islands and from all continents except antarctica. Because EPNs and their associated bacteria are safe to humans, other vertebrates, and plants, can effectively kill soil insect pests in a short time, serve as an alternative to chemical pesticides, are easily massed produced in vivo and in vitro, and do not require registration in many countries, a number of EPN species have been produced commercially to target soil and plant-boring pests in high value crops. Moreover, the associated bacteria produce antibiotics and other compounds that have potential to be used against human, veterinary, and plant pathogens. © 2017 KRF.